2018
DOI: 10.3390/rs10111847
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of BeiDou-3 Experimental Satellite Clocks

Abstract: The characteristics of the improved Atomic Frequency Standard (AFS) operated on the latest BeiDou-3 experimental satellites are analyzed from day-of-year (DOY) 254 to 281, of the year 2017, considering the following three aspects: stability, periodicity, and prediction precision. The two-step method of Precise Orbit Determination (POD) is used to obtain the precise clock offsets. We presented the stability of such new clocks and studied the influence of the uneven distribution of the ground stations on the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Their results demonstrated that the observational quality of the new-generation B1C/B2a/B2b signals from BDS-3 experimental satellites is comparable to their GPS/Galileo counterparts. Moreover, the performance of precise orbit determination, satellite clocks, precise point positioning, and relative positioning were also evaluated using observations from BDS-3 experimental satellites or together with BDS-2 satellites [2,7,8,[12][13][14][15]. Recently, several researchers have further presented their initial evaluation results for the new navigation signals transmitted by eight BDS-3 operational satellites, and similar results are also achieved as the experimental satellites [2,3,16].…”
Section: Introductionmentioning
confidence: 97%
“…Their results demonstrated that the observational quality of the new-generation B1C/B2a/B2b signals from BDS-3 experimental satellites is comparable to their GPS/Galileo counterparts. Moreover, the performance of precise orbit determination, satellite clocks, precise point positioning, and relative positioning were also evaluated using observations from BDS-3 experimental satellites or together with BDS-2 satellites [2,7,8,[12][13][14][15]. Recently, several researchers have further presented their initial evaluation results for the new navigation signals transmitted by eight BDS-3 operational satellites, and similar results are also achieved as the experimental satellites [2,3,16].…”
Section: Introductionmentioning
confidence: 97%
“…Second, the satellite clock stability differs significantly between BDS‐2 and BDS‐3. Besides, the broadcast orbit and clock parameters are separately determined by orbit determination and time synchronization (OD & TS) and two‐way satellite time and frequency transfer (TWSTFT) (Lv, Geng, Zhao, & Liu, 2018; Wu et al., 2017), which weakens the correlation between orbit errors and clock errors. Furthermore, BDS‐3 employs the inter‐satellite links (ISLs) to mitigate the challenges caused by limited ground stations, and thus, the associated SIS accuracy can be improved (Yang et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Technologies of the signal system [17], intersatellite links [18], and POD [19] were validated and analyzed. The atomic clock performance was also assessed with the clock data derived by the TWSTFT [20] or ODTS method [21,22]. Wu et al [20] analyzed the frequency stability, prediction accuracy, and clock rate variation, and the optimal stability at the averaging time of 86,400 s is 6.5 × 10 −15 for the IGSO satellite C32 with the Ka-band measurement noise of 3 × 10 −15 .…”
Section: Introductionmentioning
confidence: 99%
“…Remote Sens. 2019, 11, 2895 3 of 17Lv et al [22] analyzed the stability, periodicity, and prediction precision of BDS-3e clocks. The 10,000 s stability of C32 with PHM is 2.6 × 10 −14 , which is comparable to Galileo PHM and GPS IIF RAFS.…”
mentioning
confidence: 99%